A new species of Derris Lour. (Fabaceae: Papilionoideae) from Tamil Nadu, India. Issue 1 (2nd January 2017) - Kottaimuthu, R.; Vasudevan, N.
Abstract: A new species, Derris matthewii, is described from the dry evergreen forests of the Alagar Hills, Tamil Nadu, India. The new species closely resembles Derris ovalifolia (Wight & Arn.) Benth., but differs in leaflet shape, texture and 8–10 pairs of lateral veins, petiolule length, articulated pedicels, calyx campanulate, glabrous, and ovary glabrous.